Katolicy w potrzasku : wspomnienia z peryferii polityki - Micewski, Andrzej, 1926- (Warszawa : Polska Oficyna Wyd."BGW", 1993)
A discussion on the position of Polish Catholics in relation to the socialist state during the 45 years of socialist rule.
Keywords: Micewski, Andrzej, -- 1926-; Communism and Christianity -- Poland -- Catholic Church; Press, Catholic -- Poland; Church and state -- Poland; Poland -- Politics and government -- 1945-